+0  
 
0
224
1
avatar

1. Simplify 2-1/4 over 3-1/5, provide your answer in the lowest terms.

2. Complete the following equation (4/2)[6-(-5)3]

Guest Sep 27, 2017
 #1
avatar+90053 
+1

2 - 1/4  =   (8/4)  - (1/4)   = 7/4

 

3 - 1/5  =    (15/5)  - (1/5)   = 14/5

 

So  

 

[ 2 - 1/4 ]                           7 / 4

_______       =               _____

[ 3 - 1/5 ]                         14 / 5

 

 

Keep the fraction in the numerator.......invert the fraction in the denominator and multiply the two......so we have

 

(7 / 4 )   (   5 / 14)   =      swap denominators

 

( 7 / 14)  ( 5 / 4)   =

 

(1 /2)  ( 5 / 4)  = 

 

5  / 8

 

 

 

(4/2)[6-(-5)3]    =

 

(2) [ 6 -  (-15) ]  =

 

(2)  [ 6 + 15 ] =

 

(2) [21 ]  =

 

42

 

 

cool cool cool

CPhill  Sep 27, 2017
edited by CPhill  Sep 27, 2017

4 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.